Caveolin-1 mediates cellular distribution of HER2 and affects trastuzumab binding and therapeutic efficacy. Issue 1 (December 2018) - Pereira, Patrícia; Sharma, Sai; Carter, Lukas; Edwards, Kimberly; Pourat, Jacob; Ragupathi, Ashwin; Janjigian, Yelena; Durack, Jeremy; Lewis, Jason
Abstract Human epidermal growth factor receptor 2 (HER2) gene amplification and/or protein overexpression in tumors is a prerequisite for initiation of trastuzumab therapy. Although HER2 is a cell membrane receptor, differential rates of endocytosis and recycling engender a dynamic surface pool of HER2. Since trastuzumab must bind to the extracellular domain of HER2, a depressed HER2 surface pool hinders binding. Using in vivo biological models and cultures of fresh human tumors, we find that the caveolin-1 (CAV1) protein is involved in HER2 cell membrane dynamics within the context of receptor endocytosis. The translational significance of this finding is highlighted by our observation that temporal CAV1 depletion with lovastatin increases HER2 half-life and availability at the cell membrane resulting in improved trastuzumab binding and therapy against HER2-positive tumors. These data show the important role that CAV1 plays in the effectiveness of trastuzumab to target HER2-positive tumors. Trastuzumab binding to tumor cells depends on the availability of HER2 at the cell membrane. Here the authors show that caveolin-1 (CAV1) regulates HER2 density at the cell membranes and that CAV1 gene knockdown or protein depletion via the cholesterol modulator lovastatin, increases trastuzumab binding and anti-tumor activity.